2021
DOI: 10.2478/jeppm-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Impediments to Construction Safety Improvement

Abstract: Construction safety is one of the parameters for evaluating the success of a construction project. Evidence from the literature suggests that a poor health and safety (H&S) record is a matter of concern to project stakeholders. The benefits of improved H&S performance include, inter alia, increased productivity, reduced construction cost, reduced workplace accidents, and an enhanced industry image. This research seeks to determine major obstacles to project site safety in Nigeria. An understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…Safety management has been defined as a promotion of good safety performance and safety culture (Grote, 2012). It has also been recognized as the use safety components to manage safety policy; safety resources and responsibilities; risk identification and mitigation; standards and procedures; human factors-based system design; safety training; safety performance monitoring; incident reporting and investigation; auditing; continuous improvement; and change (Grote, 2012;Kukoyi & Adebowale, 2021;Lee & Son, 2021). These components should not only be seen as general standards but also be included in any safety management system (Grote, 2012).…”
Section: Safety Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…Safety management has been defined as a promotion of good safety performance and safety culture (Grote, 2012). It has also been recognized as the use safety components to manage safety policy; safety resources and responsibilities; risk identification and mitigation; standards and procedures; human factors-based system design; safety training; safety performance monitoring; incident reporting and investigation; auditing; continuous improvement; and change (Grote, 2012;Kukoyi & Adebowale, 2021;Lee & Son, 2021). These components should not only be seen as general standards but also be included in any safety management system (Grote, 2012).…”
Section: Safety Managementmentioning
confidence: 99%
“…At a later stage, safety management has been promoted as effective safety behaviors and practices (Okoye & Okolie, 2013). In other words, the safety management process must be well planned to enable construction site managers as well as workforces to not only identify and identify safety risks but also communicate effectively with each other during the construction processes (Kukoyi & Adebowale, 2021;Lee & Son, 2021;Park & Hyeon-Jin, 2013). Moreover, Yiu et al (2018) have identified safety management to be the management of all functions associated with carrying on activities relates to the safety of personnel including organizing, planning, developing, and implementing safety policy.…”
Section: Safety Managementmentioning
confidence: 99%
See 3 more Smart Citations